Improvement of poly(3-phenylthiophene)-based bulk heterojunction organic solar cells - Chanitpa Khantha (2018)
This paper describes the synthesis and photovoltaic studies of Poly(3-Phenylthiophene) (P3PhT). P3PhT was synthesized by the chemically oxidized polymerization in the presence of FeCl3. Bulk heterojunction solar cells based on polymer were fabricated by using chloroform, chlorobenzene, and dichlorobenzene at different weight ratios of P3PhT. The different ratios of P3PhT as the electron donor blended with [6,6]-phenyl-C61-butyric acid methyl ester (PC61BM) as the electron acceptor were investigated. A maximum power conversion efficiency was achieved at a 2:3 (wt:wt) P3PhT:PC61BM blend ratio in dichlorbenzene. Copyright © Taylor & Francis Group, LLC.